Timing of retrograde metamorphism in medium-pressure pelitic granulites of the Qianlishan Complex: insights from monazite-zircon U-Pb geochronology and phase equilibria modelling - Wu, Shangjing; Su, Yige; Wang, Qin; Qiao, Hengzhong (Frontiers in Earth Science, 2025)
Accurately determining the retrograde metamorphic ages of pelitic granulites is crucial for reconstructing their metamorphic evolution and understanding associated post-collisional extensional and subsequent exhumation processes in orogenic belts. This study integrates zircon and monazite geochronology with thermodynamic modelling to determine the retrograde metamorphic history of medium-pressure (MP) pelitic granulites in the Qianlishan Complex of the Khondalite Belt, North China Craton. Our findings show that all MP pelitic granulites follow similar clockwise pressure-temperature (P-T) trajectories, with precisely defined post-peak P-T conditions of 775°C–825°C and 4.9–6.5 kbar. U-Pb zircon dating via LA-ICP-MS on three MP granulites produced metamorphic ages of 1943 ± 18 Ma, 1931 ± 10 Ma, and 1941 ± 10 Ma. Similarly, monazite U-Pb analyses of the same samples yielded ages of 1932 ± 3 Ma, 1935 ± 3 Ma, and 1939 ± 3 Ma. A well-matched set of dates indicates a metamorphic episode at ∼1.93 Ga, which established a metamorphic period during the granulite-facies retrograde cooling phase. The geochronological studies of pelitic granulites from the Qianlishan Complex indicate that a peak-pressure metamorphic event took place between 1.96 and 1.94 Ga, with subsequent decompression and retrograde cooling occurring around 1.93 Ga. These findings reinforce the hypothesis that a continent-continent collision occurred in the Khondalite Belt around 1.95 Ga, followed by a rapid slab-breakoff at shallow depths, which triggered the uplift of pelitic granulites in the western Khondalite Belt to mid-crustal levels and their subsequent cooling around 1.93 Ga.